Short-term head-down bed rest microgravity simulation alters salivary microbiome in young healthy men - Sun, Hui; Zhou, Qian; Qiao, Pengyan; Zhu, Di; Xin, Bingmu; Wu, Bin; Tang, Chuhua (Frontiers in Microbiology, 2022)
Microgravity influences are prevalent during orbital flight and can adversely affect astronaut physiology. Notably, it may affect the physicochemical properties of saliva and the salivary microbial community. Therefore, this study simulates microgravity in space using a ground-based −6° head-down bed rest (HDBR) test to observe the effects of microgravity on oral salivary secretion function and the salivary microbiome. Sixteen healthy young male volunteers were recruited for the 15-day −6° HDBR test. Non-stimulated whole saliva was collected on day 1 (pre-HDBR), on days 5, 10, and 15 of HDBR, and day 6 of recovery. Salivary pH and salivary flow rate were measured, and the V3–V4 region of the 16S RNA gene was sequenced and analyzed in 80 saliva samples. The results showed that there were no significant differences in salivary pH, salivary flow rate, and alpha diversity between any two time points. However, beta diversity analysis revealed significant differences between pre-HDBR and the other four time points. After HDBR, the relative abundances of Actinomyces, Parvimonas, Peptostreptococcus, Porphyromonas, Oribacterium, and Capnocytophaga increased significantly, whereas the relative abundances of Neisseria and Haemophilus decreased significantly. However, the relative abundances of Oribacterium and Capnocytophaga did not recover to the pre-HDBR level on day 6 of recovery. Network analysis revealed that the number of relationships between genera decreased, and the positive and negative correlations between genera changed in a complex manner after HDBR and did not reach their original levels on day 6 of recovery. PICRUSt analysis demonstrated that some gene functions of the salivary microbiome also changed after HDBR and remained significantly different from those before HDBR on day 6 of recovery. Collectively, 15 days of −6° HDBR had minimal effect on salivary secretion function but resulted in significant changes in the salivary microbiome, mainly manifested as an increase in oral disease-related bacteria and a decrease in oral health-related commensal bacteria. Further research is required to confirm these oral microbial changes and explore the underlying pathological mechanisms to determine the long-term effects on astronauts embarking on long-duration voyages to outer space.